2022
DOI: 10.1371/journal.pone.0271091
|View full text |Cite
|
Sign up to set email alerts
|

Capsicum annuum with causal allele of hybrid weakness is prevalent in Asia

Abstract: Reproductive isolation, including hybrid weakness, plays an important role in the formation of species. Hybrid weakness in Capsicum, the cessation of plant growth, is caused by two complementary dominant genes, A from C. chinense or C. frutescens and B from C. annuum. In the present study, we surveyed whether 94 C. annuum accessions had B or b alleles by crossing with C. chinense having the A allele. Of the 94 C. annuum accessions, five had the B allele, three of which were native to Latin America and two were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The general symptoms of hybrid lethality are apparent death of seedlings and are typically observed in interspecific hybridizations in Nicotiana ( Yamada et al., 1999 ; Tezuka, 2012 ; Tezuka, 2013 ). Hybrid weakness is characterized by the weak growth of seedlings compared to both parents and is typically observed in Oryza ( Chu and Oka, 1972 ; Chen et al., 2013 ; Nadir et al., 2019 ; Shiragaki et al., 2019 ), Capsicum ( Shiragaki et al., 2020b ; Shiragaki et al., 2021 ; Shiragaki et al., 2022 ), and Phaseolus ( Koinange and Gepts, 1992 ; Reiber and Neuman, 1999a ). Hybrid necrosis may refer to both types and is mainly used for the Triticum - Aegilops complex ( Tsunewaki and Kihara, 1962 ; Toxopeus and Hermsen, 1964 ; Mizuno et al., 2010 ; Zhang et al., 2022b ) and Arabidopsis ( Bomblies et al., 2007 ; Świadek et al., 2017 ).…”
Section: Hybrid Seedling Lethalitymentioning
confidence: 99%
“…The general symptoms of hybrid lethality are apparent death of seedlings and are typically observed in interspecific hybridizations in Nicotiana ( Yamada et al., 1999 ; Tezuka, 2012 ; Tezuka, 2013 ). Hybrid weakness is characterized by the weak growth of seedlings compared to both parents and is typically observed in Oryza ( Chu and Oka, 1972 ; Chen et al., 2013 ; Nadir et al., 2019 ; Shiragaki et al., 2019 ), Capsicum ( Shiragaki et al., 2020b ; Shiragaki et al., 2021 ; Shiragaki et al., 2022 ), and Phaseolus ( Koinange and Gepts, 1992 ; Reiber and Neuman, 1999a ). Hybrid necrosis may refer to both types and is mainly used for the Triticum - Aegilops complex ( Tsunewaki and Kihara, 1962 ; Toxopeus and Hermsen, 1964 ; Mizuno et al., 2010 ; Zhang et al., 2022b ) and Arabidopsis ( Bomblies et al., 2007 ; Świadek et al., 2017 ).…”
Section: Hybrid Seedling Lethalitymentioning
confidence: 99%
“…A study reported a wider range (2%-91%) of outcrossing, with chili as suggested as a crosspollinating crop species (Ritonga et al, 2018). Natural and artificial selection (variety development by breeder) can bring diversity to the chili gene pool (Shiragaki et al, 2022). Moreover, interspecific cross-compatibility between cultivated capsicum species (Barchenger et al, 2019) may have developed interspecific hybrids (Bosland and Baral, 2007), contributing to the genetic diversity.…”
Section: Genetic Diversity and Distribution Of Chili In Nepalmentioning
confidence: 99%
“…A typical example of postmating-prezygotic barriers is the cross-incompatibility between pollen and pistils [4][5][6][7][8][9][10][11]. Postzygotic barriers include hybrid seed abortion [4,, hybrid weaknesses [37][38][39][40][41][42][43][44][45][46][47], hybrid lethality [32,[48][49][50][51][52][53][54][55][56][57][58][59][60] or necrosis [61][62][63][64][65][66][67][68][69][70][71], and hybrid sterility [72][73][74][75][76]…”
Section: Introductionmentioning
confidence: 99%